CO tolerance of Pt and PtSn intermetallic electrocatalysts on synthetically modified reduced graphene oxide supports. Issue 3 (18th November 2014) - Sims, Christopher M.; Ponce, Audaldo A.; Gaskell, Karen J.; Eichhorn, Bryan W.
Abstract : Electrochemical studies demonstrated the ability to modify the catalytic activities of graphene supported Pt and PtSn nanoparticle electrocatalysts by altering the nature of the metal-support interactions. Abstract : Pt and PtSn intermetallic nanoparticle (NP) catalysts were grown directly on various reduced graphene oxide (rGO) supports and were characterized by a combination of X-ray photoelectron spectroscopic (XPS), Raman microscopy, transmission electron microscopy (TEM), and powder X-ray diffraction (XRD) studies. Electrochemical CO stripping and rotating disk electrochemical (RDE) experiments showed the four rGO-PtSn catalysts to be superior to the four rGO-Pt catalysts for CO and CO–H2 electrooxidation in acidic solutions regardless of the rGO support, in agreement with earlier reports on PtSn NP electrocatalysts. For the four rGO-Pt catalysts, the rGO support causes a 70 mV spread in CO oxidation peak potential (Δ E peak ) and a 200 mV spread in CO–H2 electrooxidation onset. The more oxygenated graphenes show the lowest CO oxidation potentials and the best CO tolerance. For the four rGO-PtSn intermetallic catalysts, a ∼160 mV spread in CO–H2 electrooxidation onset is observed. With the exception of the nitrogen-doped graphene (NGO), a similar trend in enhanced CO electrooxidation properties with increasing oxygen content in the rGO support is observed. The NGO-PtSn electrocatalyst was superior to the other rGO-PtSn catalysts and showed the largest improvement in CO tolerance relative to the pure Pt system. The origin of this enhancement appears to stem from the unique rGO-PtSn support interaction in this system. These results are discussed in the context of recent theoretical and experimental studies in the literature.